2015
DOI: 10.3109/09540261.2015.1085369
|View full text |Cite
|
Sign up to set email alerts
|

Institutionally based videoconferencing

Abstract: The delivery of psychiatric care via video-teleconferencing (VTC) technology is thought to have reached a tipping point. As a medical speciality with relatively few material or technical requirements for service delivery, psychiatry has been one of the earliest to embrace the possibility of providing evaluations and treatment at a distance. Such technical infrastructure as is necessary can often be found in the institutions already in existence. It was natural therefore that institutionally based telepsychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…3 Telepsychiatry (ie, 2-way video) provides access to psychiatric care, enhanced quality of care, and reduced health care costs. [4][5][6] An increasing body of literature reports effectiveness and outcomes equivalent to in-person care across a broad range of mental health disorders and patient populations. [4][5][6] In some situations (such as working with children and teens), telepsychiatry may even be preferable to in-person care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Telepsychiatry (ie, 2-way video) provides access to psychiatric care, enhanced quality of care, and reduced health care costs. [4][5][6] An increasing body of literature reports effectiveness and outcomes equivalent to in-person care across a broad range of mental health disorders and patient populations. [4][5][6] In some situations (such as working with children and teens), telepsychiatry may even be preferable to in-person care.…”
mentioning
confidence: 99%
“…[4][5][6] An increasing body of literature reports effectiveness and outcomes equivalent to in-person care across a broad range of mental health disorders and patient populations. [4][5][6] In some situations (such as working with children and teens), telepsychiatry may even be preferable to in-person care. [7][8][9][10][11][12] Despite many studies reporting positive clinician and patient satisfaction with telepsychiatry, 8,9,11,13,14 implementation has not been rapid, easy, or widespread.…”
mentioning
confidence: 99%
“…The quantitative outcomes data reported varied from correlation between in-person/telemedicine assessment scores, 38 numbers of consultations, 39–42 patient satisfaction scores, 43 cost effectiveness, 34,44–50 and clinical outcome measures. 51–52 Very few studies reported outright failures of telemedicine, 53–54 with most finding it offered equivalent or improved care quality 5,42,43,51,52,55–70 at an acceptable cost. 8,9,25,31,34,38,43,47,50,53,56–59,62,64,69…”
Section: Resultsmentioning
confidence: 99%
“…There is a large body of evidence which demonstrates their effectiveness at improving the access and cost of healthcare provision in prisons 13. The more limited data on patient experience suggests it also offers improved care quality for prisoners 14–17…”
Section: Introductionmentioning
confidence: 99%